Contribution of the Western Australian wheatbelt termite, Drepanotermes tamminensis (Hill), to the soil nutrient budget - Park, H.; Majer, Jonathan; Hobbs, R. (1994)
The role of soil modification by the mound-building termite, Drepanotermes tamminensis (hill), was studied during 1991 in the Durokoppin Nature Reserve, Western Australia. Soil chemical parameters were quantified for 'soils' in nests and for surrounding soil in both a Wandoo (Eucalyptus capillosa) woodland and a Casuarina (Allocasuarina campestris) shrubland plot. All 'soils' in nests were more acidic than the un-nested soil within each study plot and were also higher in the woodland than in the shrubland plot. Depending on the nutrient concerned, the nested soil contained between 0.3 and 21.9% of the total nutrient load per hectare within each study plot. The quantities of nutrients per hectare in termite mounds were higher in the woodland than in the shrubland plot. It is concluded that mounds of this species of termite form a significant bank of nutrients, although time for release of such nutrients depends on the degree of erosion and on the longevity of mounds.